PENGARUH TEKNOLOGI SISTEM INFORMASI TERHADAP EFISIENSI KINERJA PEGAWAI KANTOR DESA RIJANG PANUA - Virna Rusli, Widya; Muhammad Ikbal; Sundari (Universitas Bina Taruna Gorontalo, 2025)
This study aims to determine the effect of information system technology usage on the efficiency of employee performance at the Village Office of Rijang Panua, Kulo District, Sidenreng Rappang Regency. The research employed a quantitative approach using a simple linear regression analysis method. Data were collected through questionnaires distributed to all village employees as respondents. The results indicate that the use of information system technology has a significant effect on work efficiency, with a significance value of 0.000 and a coefficient of determination (R²) of 0.336. This means that 33.6% of the variation in employee performance efficiency can be explained by the application of information technology. The findings suggest that the integration of information systems supports faster workflows, improved accuracy, and more efficient public services. The conclusion of this study is that information technology plays an important role in improving the efficiency of village staff performance. However, its successful implementation requires the readiness of human resources and supporting infrastructure..